Co-evolution of primitive methane-cycling ecosystems and early Earth’s atmosphere and climate - Boris Sauterey; Benjamin Charnay; Antonin Affholder; Stéphane Mazevet; Régis Ferrière (Nature Communications, 2020)
Biology can profoundly influence the planet’s climate, but over Earth’s long history these effects are poorly constrained. Here the authors show that on early Earth, the evolution of microbes producing and consuming methane likely controlled warming and glacial events, and thus Earth’s habitability